PENDAMPINGAN PENGAWAS PENDIDIKAN AGAMA ISLAM PADA IMPLEMENTASI KURIKULUM 2013 DI MADRASAH SE-KOTA METRO LAMPUNG - Umam, Aguswan Khotibul; Chasanatin, Haitin; Sudin, Mokhtaridi (JURNAL TAPIS, 2015)
ABSTRACTThis research is aimed at describing the supervision of the implementation of 2013 curriculum critically and qualitatively by PAI supervisor toward headmaster and teachers of Madrasah in Metro city. The data collecting techniques used in this research are observation, interview, and documentation. The results of the research are (1) supervision toward madrasah headmaster through socialization of 2013 curriculum, formation of madrasah development team, technical guidance, madrasah self-evaluation, arrangement of medium working plan 2014-2019, arrangement of working plan 2014-2015, intensification of madrasah curriculum development team, arrangement of 2013 curriculum and its legalization process, and guidance of madrasah pre-accreditation. (2) Supervision toward madrasah teachers though socialization, technical guidance of 2013 curriculum, formation and intensification of MGMP activity, and administration, academic, and clinical supervision according to each subject especially to scoring model and authenticity. Keywords: Supervision, PAI supervisor, implementation, 2013 curriculum, madrasah.